Some Hematological and Histological Impact of sub-acute exposure to Mono Sodium Glutamate in Mice: Orooba M.S. Ibrahim1, Nibras Naaib Abdulhamza1 and Hana Khudair Abbass2 - Ibrahim, Orooba M.S. (The Iraqi Journal of Veterinary Medicine, 2012)
Mono Sodium Glutamate (MSG) is a food additive commonly consumed as a flavor enhancer. However, both animal models and human clinical reports have established its harmful effects. The present study aimed to investigate the effect of MSG consumption on some hematological parameters and histological sections of brain, small intestine, liver and testis tissues of Swiss Albino mice. Albino mice (n=15) of average weight 27.4gm were randomly assigned into three groups A, B and C in each group (n=5). Treatment groups (A & B) were given 3g and 6g per Kg of body weight of MSG (amount of MSG in a single sachet consumed by human is 3g) respectively. The mice were sacrificed on day fifteenth of the experiment. Brain, small intestine, liver and testis were carefully dissected out and immediately fixed in 10% formalin for routine histological procedure. Blood samples were analyzed for hematological parameters. Histological findings of small intestine in the treated groups showed evidence of cellular hypertrophy and increased number of goblet cells. Large nuclei with multi nucleoli were seen in liver sections, while prevascular and preneuronal edema were seen in brain sections and thickening of basement membrane of semineferons tubules. Vacuolation of spermatogonia were seen in testicular tissue sections. Blood analysis showed a significant increase at P>0.01 in lymphocytes count compared to the control which can be considered indication of a compromised immune status and poisoning in the treated animals. Packed Cell Volume (PCV) hemoglobin (Hb) and red blood cells count (RBCs) were all indicative of an anemic condition in the treated animals. Significant increase in body weight at P>0.01 was seen in both treatment groups (A & B). All above findings indicate that MSG has some deleterious effects on some hematological parameters and caused histological changes of examined organs as well as on body weight. It is recommended that further studies aimed at corroborating these findings to be carried out.